A comparison of growth and dietary adequacy of children with celiac disease on a gluten-free diet with their healthy-peers at a tertiary care center in Turkey - Ekşi, Neslihan; Bozbulut, Rukiye; Köksal, Eda; Dalgıç, Buket (Frontiers in Pediatrics, 2025)
IntroductionCeliac disease (CD) is a chronic autoimmune disorder that requires strict adherence to a gluten-free diet (GFD) initiated after diagnosis. This limited diet may lead to nutritional deficiencies. The aim of this study was to evaluate nutritional intake and dietary adequacy of children with CD having good adherence to a GFD compared with their healthy peers and to assess the contribution of commercial gluten-free products on the daily energy and macronutrient intakes.MethodsThis cross-sectional case-control study included children with CD (age range, 2–18 years) and age- and sex-matched healthy controls. Demographic characteristics, anthropometric measurements and food consumption (3-day food record) were recorded. The groups were compared for dietary compositions, dietary adequacy, and anthropometric parameters.ResultsThe study compared 51 patients with 54 controls. The patients had significantly lower height-for-age Z-scores and body mass index-for-age Z-scores (p < 0.05). The dietary daily energy, protein, fat and fiber intakes were significantly lower in the patients than in the healthy controls (p < 0.05). The mean nutrient adequacy ratio (NAR) for protein, thiamine, calcium, magnesium, iron, zinc and fiber was significantly lower in the patients for both sexes (p < 0.05 for all) and the mean NAR for vitamin A and folate was lower in the patients in females (p < 0.05 for all). The mean nutrient adequacy ratio (MAR) of protein, thiamine, calcium, magnesium, iron, zinc and fiber was lower in the patients than in the controls (p < 0.05 for all).ConclusionA comprehensive dietary assessment for patients with CD may enhance their adaptation to healthy nutrition and facilitate their optimal growth.